Successful Root Canal Re-treatment of the Second Mandibular Premolar with type III of Vertucci Classification - Sofiani, Erma; Setyawan, Erwin (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2024)
Knowledge of the root canal system plays a significant role in avoiding the failure of root canal treatment. Premolar teeth may have several anatomical variations in their root canal system. A dentist must understand these root canal systems and their variation to conduct the appropriate treatment. The mandibular second premolar usually consists of a single root with a single root canal. The incidence of lower premolars with two or more root canals varied between 1.2% and 34%. This study aims to evaluate the success of root canal re-treatment of mandibular second premolars with type III Vertucci’s Classification. Case report: A 28-year-old woman visited our dental hospital with a pain sensation in her lower left premolar tooth. The subjective examination revealed that she had experienced pulp capping and root canal treatment last year. However, she felt pain and uncomfortable feeling on that treated tooth. A radiograph examination showed a radiopaque area from the crown edge to half of the root. The radiolucent area from the half tooth to the apical region showed root canal branching. The diagnosis for this tooth was previously treated teeth, asymptomatic apical periodontitis with type III of Vertucci’s Classification. Root Canal Treatment was done using crown down preparation technique and obturation with warm vertical condensation followed by class II composite resin composite as a temporary filling. Results showed that after three months of evaluation, the retreated-tooth condition kept showing good condition without any complaints, pain, or clinical abnormalities, suggesting it could function properly.